The political theory of reinvention - Deleon, Linda; Denhardt, Robert B. (2000)
In this article, we examine the implications of the reinvention movement for democratic governance, broadly defined. The most basic premise of the reinvention movement is a belief that the accumulation of the narrowly defined self-interests of many individuals can adequately approximate the public interest. By "narrowly defined," we mean the interests of individuals as they privately apprehend them, unmediated by participation in a process of civic discourse. To illustrate the centrality of this assumption to the implicit theory of reinvention, we consider three of its elements - its use of the market model, its emphasis on customers rather than citizens, and its glorification of entrepreneurial management. We then examine the implications of the self-interest assumption, which entails a rejection of democratic citizenship, civic engagement, and the public interest, broadly conceived. - Reproduced
Keywords: Administrative reform; Public administration